Neonatal citrobacter meningitis - Gwynn, C. M. (1973)
An epidemic involving 4 babies with neonatal meningitis due to Citrobacter koseri is described. Only 1 of the 4 babies made a full recovery: 2 others survived with severe permanent brain damage after a prolonged illness, and the fourth baby died after a short fulminating infection.